PEMANFAATAN MEDIA FLASHCARD DALAM PEMBELAJARAN MEMBACA PERMULAAN DI KELAS II SDN CUKANGGALIH 1 KABUPATEN TANGERANG - Audy Maulidya; Mujazi Mujazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The early reading skills of second-grade students at SDN Cukanggalih 1, Tangerang Regency, are still relatively low, as indicated by difficulties in recognizing letters, reading simple words, and connecting sounds with written text. This situation demands engaging learning media that are appropriate to the characteristics of elementary school students, one of which is flashcards. This study aims to describe the use of flashcards in early reading instruction at second-grade students at SDN Cukanggalih 1. The research method used a descriptive qualitative approach, with the second-grade teacher and one student as subjects. Data were obtained through interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the use of flashcards helped students recognize letters, string together syllables, read simple words, and connect sounds with written text. This media also increased students' motivation, concentration, and memory in reading. Teachers considered flashcards effective because they suited the characteristics of elementary school students who enjoy visuals and games.